Still here : exhibition catalogue : a brief history of Aborigines in Melbourne's western region up to the present day - Walsh, Larry; Melbourne's Living Museum of the West. (Victoria : Melbourne's Living Museum of the West, 1996)
Contains most of the text and selected images contained in the exhibition; provides a brief history of the early struggles of the Aborigines in the western suburbs of Melbourne up to the present day, told from their perspective; includes information on Aboriginal activism, the stolen generations and the resurgence of cultural activity in the area.
Includes bibliographical references (p. 56).
Keywords: Aboriginal Australians -- Victoria -- Melbourne Metropolitan Area -- History -- Exhibitions; Cultural heritage - Protection - Museums and keeping places; History; Child welfare - Child / parent separation - Stolen generations; Politics and Government - Political action - Indigenous political parties; Politics and Government - Political action - Activism; Art - Catalogues; Art - Exhibitions; Melbourne (Vic SJ55-05)